Ex ante evaluation of conservation agriculture (CA)-based systems in Zambia - CGIAR Research Program on Maize (2019)
average changes in yield from using CA-based systems at the district scale ranged from −37% to 70% (average 33%), with a similar range of changes in benefit-cost ratios,